Vanadium and Chromium Impact to Microstructure of AlSi10MgMn Alloy with Elevated Iron Content - Zihalova, Maria; Bolibruchova, Dana (Manufacturing Technology Journal, 2014)
In Al-Si alloys iron as an impurity causes decreasing of mechanical and foundry properties of castings. Nowadays is paid attention to adding different elements into aluminium alloys to increase the properties of final castings. Some elements eliminates iron by changing iron intermetallic phase morphology, decreasing its extent and by improving alloy properties. Also there is a possibility of using lower amounts of more elements, what can lead to change of morphology and to improve casting properties at the same time. The contribution is devoted to vanadium and combined vanadium and chromium impact to AlSi10MgMn alloy with high iron level. This effect is evaluated through microstructural analysis using different etchants. Colour metallography is also used to find the better and faster identification of the intermetallic phases.
Keywords: Secondary Al alloys; Iron influence; Vanadium; Mutual V and Cr influence; Microstructure